KASUS SECTIO CAESARIA ANJING DAN KUCING DI RUMAH SAKIT HEWAN PROFESOR SOEPARWI TAHUN 2012 - , TALITA OLISIYA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Job Training in Animal Hospital Professor Soeparwi held April 1-6, 2013. The Job Training goal is to study the case of a cesarean section in dogs and cats RSH Prof. Soeparwi years 2012.Data caesarean cases dogs and cats obtained from the accounting data / medical records of patients in RSH Prof. Soeparwi during 2012 and conducted interviews of employees, Prof. RSH. Soeparwi. Number of cases of cesarean section were obtained during the year 2012 recorded 52 cases of caesarean section, consisting of 45 cases of cesarean section in dogs and 7 cases of cesarean section in cats. Caesarean section is the cause of them have a dead fetus in the womb, distokia, the inability of the parent to push, the size of the fetus is too large and the demand of the client. Percentage of the existing results, in patients Cesareans most dogs do on the grounds that the client desires 48.89%, while the cats do Caesarean section with no reason that dead fetus in the womb is 57.14%.